Impact of baseline serum ferritin and supplemental iron on altitude-induced hemoglobin mass response in elite athletes - Koivisto-Mørk, A. E.; Svendsen, I. S.; Skattebo, Ø.; Hallén, J.; Paulsen, G. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The present study explored the impact of pre-altitude serum (s)-ferritin and iron supplementation on changes in hemoglobin mass (DeltaHbmass) following altitude training. Measures of Hbmass and s-ferritin from 107 altitude sojourns (9-28 days at 1800-2500 m) with world-class endurance athletes (males n = 41, females n = 25) were analyzed together with iron supplementation and self-reported illness. Altitude sojourns with a hypoxic dose [median (range)] of 1169 (912) km·h increased Hbmass (mean ± SD) 36 ± 38 g (3.7 ± 3.7%, p < 0.001) and decreased s-ferritin -11 (190) µg·L-1 (p = 0.001). Iron supplements [27 (191) mg·day-1] were used at 45 sojourns (42%), while only 11 sojourns (10%) were commenced with s-ferritin <35 µg/L. Hbmass increased by 4.6 ± 3.7%, 3.4 ± 3.3%, 4.2 ± 4.3%, and 2.9 ± 3.4% with pre-altitude s-ferritin =35 µg·L-1, 36-50 µg·L-1, 51-100 µg·L-1, and >100 µg·L-1, respectively, with no group difference (p = 0.400). Hbmass increased by 4.1 ± 3.9%, 3.0 ± 3.0% and 3.7 ± 4.7% without, =50 mg·day-1 or >50 mg·day-1 supplemental iron, respectively (p = 0.399). Linear mixed model analysis revealed no interaction between pre-altitude s-ferritin and iron supplementation on DeltaHbmass (p = 0.906). However, each 100 km·h increase in hypoxic dose augmented DeltaHbmass by an additional 0.4% (95% CI: 0.1-0.7%; p = 0.012), while each 1 g·kg-1 higher pre-altitude Hbmass reduced DeltaHbmass by -1% (-1.6 to -0.5; p < 0.001), and illness lowered DeltaHbmass by -5.7% (-8.3 to -3.1%; p < 0.001). In conclusion, pre-altitude s-ferritin or iron supplementation were not related to the altitude-induced increase in Hbmass (3.7%) in world-class endurance athletes with clinically normal iron stores.